Trophic structure of fish communities in mangrove systems subject to different levels of anthropogenic intervention, Tropical Eastern Pacific, Colombia - Medina-Contreras, Diana; Cantera-Kintz, Jaime; Sánchez, Alberto (Environmental science and pollution research international, 2022)
Mangroves are important ecosystems of tropical and subtropical shorelines. Anthropogenic activity decreases their habitat quality, affecting structural and functional trophic features. We hypothesized that higher levels of anthropogenic intervention generate diversity loss and modify the trophic structure of tropical mangrove fish communities. We compared the taxonomic and isotopic (δ 13 C/δ 15 N) composition, abundance, trophic position, and isotopic niche of fish communities from three mangrove systems with different anthropogenic intervention levels in the Colombian Pacific. Non-parametric statistical tests and a Bayesian approach were used to analyze data. A total of 1254 specimens belonging to 23 families, 25 genera, and 30 species were identified, presenting higher abundance (821) in moderate anthropogenic intervention level mangrove (Moderate-AIL), with high dominance of one species ( Lile stolifera ). The low anthropogenic intervention level mangrove (Low-AIL) was the second in abundance (291) but exhibited a greater number of species (23), while the high anthropogenic intervention level mangrove (High-AIL) presented the least abundance (142) and species number (17). The isotopic composition ​​reveals that Moderate and High-AIL mangroves presented enriched 13 C and 15 N compared to Low-AIL (~ 2 to 4 ‰). Mean trophic position (TP) of communities was slightly higher in the more intervened systems (~ 1 to 2 orders of magnitude), as well as in specific species ( Centropomus spp . ). Isotopic niche width (TA and SEAc) was greater in High-AIL (41.1 and 9.2), more than doubled compared to Moderate-AIL (33.0 and 4.1). In High-AIL isotopic niche width increased, indicating lesser availability of prey and basal resources. The results obtained in this study support the proposed hypothesis and, suggest that anthropogenic intervention modifies diversity and food webs dynamics, affecting the transfer of matter and energy from macrotidal tropical mangroves to coastal ecosystems. However, it is recommended to be careful concluding differences based exclusively on the anthropogenic intervention level, since it is widely documented that mangrove settings also influence the analyzed trophic parameters.